Evaluation of a web-based tobacco cessation counseling program among third year medical students of private medical universities in northern Malaysia - Nyi Nyi, Naing; K.K., Nyo; Z., Ahmad; R., Jaafar (2017)
People should avoid unhealthy behaviours such as smoking. Muslims are forbidden from smoking because it's harmful to health. This provision can be used in tobacco control programs for Muslims. A cross-sectional study was conducted among medical students on their knowledge and perception of religion in tobacco control. A web-based Tobacco Cessation Program (WTCC) was developed, including a module on “religion in tobacco control” and implemented to medical students. The effectiveness of the module in improving knowledge and perceptions of tobacco control among Malay medical students was studied using a validated self-administered questionnaire. The results were analysed by Generalised Estimating Equation modeling (GEE). Of the 176 Malay students, 96 (54.5%) were males and 80 (45.5%) were females. There was significant improvement in knowledge scores of the role of religion in tobacco cessation of the intervention group between before and after the intervention (p <0.001). There was also significant improvement in positive religious beliefs and perceptions scores in the role of religion between the intervention group and control group (p <0.001). The module on “religion in tobacco control” increased knowledge and improved religious beliefs and perceptions towards tobacco control among the medical students. Also, the module played a significant role in inspiring Malay medical students towards tobacco control in Malaysia.